Language Games and Language Teaching in Kenya: The case of Kiswahili in Lower Primary - Mwangi, Iribe P.I; Mutua, B.F (Journal of Education and Practice, 2014)
Many experienced textbook and methodology manuals writers have argued that games are not just time-filling activities but have a great educational value. W. R. Lee holds that most language games make learners use the language instead of thinking about learning the correct forms Language games can lower anxiety, thus making the acquisition of input more likely. They are highly motivating and entertaining, and they can give shy students more opportunity to express their opinions and feelings. The purpose of this paper is to examine the impact of using language games in teaching lower primary. The paper adopts a quasi experimental design and thus uses a pre test and post test. It has been appropriate to analyse the treatment effect of using language games in teaching lower primary learner in one group while applying the natural teaching methods on the control group. The target population is four primary schools which are sampled in Machakos town and four other primary schools sampled in the rural area of Machakos. A standardized examination is given to the two groups of lower primary learners from different localities and results recorded. Another examination was given after the treatment of teaching one group using language games. Methods used by the teachers to teach the Kiswahili Language to lower primary learners are mainly assignments and group discussions. The paper recommends that other strategies for teaching lower primary learners may include teacher assistance teams and shorter assignments. Ultimately, this paper suggests that use of language games in teaching lower primary school learners can improve their academic performance.
Keywords: Teaching aids; Teacher competence; Attitude; Self concept; Instructural resources; stimulus; Mediated learning